Discourse Analysis of Persuasive Language Techniques for Eco-Friendly Products in Instagram Captions - Christina Maya Iriana Sari; Dwi Aji Prajoko; Arielia Yustisiana (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This study examines the persuasive language techniques used by Plepah, an eco-friendly packaging company, in its Instagram captions. Plepah is a provider of biodegradable food packaging. Using discourse analysis, the research explores how Plepah communicates its mission of sustainability through the framework of Kotler’s AIDA model (Attention, Interest, Desire, Action). Using Kotler’s AIDA model, this study finds out that examines how Plepah communicates its values and encourages behavioral change among its audience.The findings highlight the potential of persuasive language in promoting eco-friendly practices and suggest best practices for brands seeking to connect with sustainability-conscious audiences.